Behavioral Neuroscience of Stress Resilience: Insights from Animal Models - K. Geetha; M. Babylatha (Frontiers in Life Sciences Research, 2025)
Stress resilience, defined as the capacity to adaptively withstand and recover from adverse experiences without developing psychopathology, has become a central focus in behavioral neuroscience due to its profound implications for mental health and disease prevention. While traditional research has primarily examined vulnerability to stress, emerging work underscores resilience as an active and dynamic process shaped by complex interactions among neural circuits, molecular pathways, and behavioral strategies. Animal models have proven indispensable in this field, offering controlled environments to systematically dissect genetic, environmental, and neurobiological variables that contribute to adaptive outcomes. Rodent paradigms such as chronic social defeat stress (CSDS) and chronic unpredictable mild stress (CUMS), along with primate and zebrafish models, provide valuable platforms for studying individual differences in coping strategies, neuroplasticity, and physiological responses. Evidence consistently highlights the pivotal role of the prefrontal cortex–amygdala–hippocampus network in regulating emotional and cognitive responses, with resilient phenotypes characterized by enhanced top-down control, hippocampal neurogenesis, and reduced maladaptive fear generalization. On a molecular level, resilience is associated with adaptive modulation of monoaminergicsignaling, upregulation of brain-derived neurotrophic factor (BDNF), balanced glucocorticoid receptor activity, and protective epigenetic modifications that buffer against stress-induced maladaptations. In parallel, immune and neuroendocrine systems interact with neural circuits to influence resilience, with reduced pro-inflammatory cytokine activity and regulated hypothalamic–pituitary–adrenal (HPA) axis reactivity emerging as critical determinants. Importantly, these mechanistic insights have translational significance, informing biomarker discovery and guiding the development of interventions such as exercise, enriched environments, pharmacological agents, and neurostimulation strategies aimed at enhancing resilience in at-risk populations. Looking forward, the integration of multimodal approaches—including genomics, connectomics, and systems neuroscience, and artificial intelligence modeling— holds promise for advancing personalized neurotherapeutics. Collectively, insights from animal models provide a robust framework for understanding stress resilience and lay the groundwork for innovative strategies to mitigate the global burden of stress-related disorders.